Optimal algorithms for the charge equalisation controller of series connected lithium-ion battery cells in electric vehicle applications - Hoque M.M.; Hannan M.A.; Mohamed A. (Institution of Engineering and Technology, 2023)
Charging (batteries); Controllers; Electric batteries; Electric machine control; Electric vehicles; Equalizers; Optimization; Particle swarm optimization (PSO); Secondary batteries; Voltage control; Control techniques; Discontinuous current mode; Flyback converters; Optimal algorithm; Particle swarm optimisation; PI controller parameters; Switching signals; Vehicle applications; Lithium-ion batteries